Animations of Ancient Vase Scenes in the Classics Classroom. Issue 31 (18th June 2015) - Nevin, Sonya
Abstract : 'That's amazing! I can see what he's doing.' These words, from a thirteen-year old boy in London, were extremely encouraging. Moments earlier he had been complaining that our imminent ancient history session would stop him playing pool. At his words, his friends looked up from online gaming, and they too began taking an interest in images of ancient vases and learning about ancient warfare. An hour later they hit the pool tables, but for the duration of our after-school session, these reluctant learners had engaged well and taken real pleasure in finding out about the ancient world.